Computer game-based mathematics education: Embedded faded worked examples facilitate knowledge acquisition. (August 2017) - ter Vrugte, Judith; de Jong, Ton; Vandercruysse, Sylke; Wouters, Pieter; van Oostendorp, Herre; Elen, Jan
Abstract: This study addresses the added value of faded worked examples in a computer game-based learning environment. The faded worked examples were introduced to encourage active selection and processing of domain content in the game. The content of the game was proportional reasoning and participants were 12- to 15-year-old students from prevocational education. The study compared two conditions in which students worked with the environment with faded worked examples (n = 49) or without worked examples (n = 44). The students who received the faded worked examples performed better on a posttest measuring their proportional reasoning skills, and this performance was related to the number of times they had interacted with the worked examples. Though already effective, there is still room for improvement which potentially can be found in the level of explanation given in the worked example before this was faded. Highlights: Prevocational students can benefit from a game-based learning environment with faded worked-examples. Embedded faded worked examples enhanced their knowledge acquisition. Faded worked examples facilitated in-game and domain knowledge post-test performance. Interaction with the faded worked examples was a significant predictor of post-test performance.